Views of Pharmacists and Government Representatives Toward the Pilot Chief Pharmacist System in Chinese Hospitals: A Multicenter Exploratory Qualitative Study - Yang, Ruomeng; Li, Qian; Hayat, Khezar; Zhai, Panpan; Liu, Wenchen; Chen, Chen; Saeed, Amna; Chang, Jie; Li, Pengchao; Du, Qianqian; Xu, Sen; Wen, Jun; et al. (Frontiers in Public Health, 2022)
Background: In China, the pharmacy departments of most hospitals have changed their main focus from drug procurement and distribution to providing pharmaceutical care services. Various regions of China have successively implemented the pilot Chief Pharmacist System (CPS) to help improve pharmaceutical services and rational drug use in hospitals. This study was designed to explore the perspectives of pharmacists and government officials on CPS, including the advantages and barriers to successful implementation of CPS. Methods: A qualitative study, based on semi-structured interviews, was conducted from October 1, 2018 to March 1, 2019. The interview data were gathered from 18 pharmacy staff and government representatives working in five distinct regions of China using purposive sampling. A thematic analysis approach and NVivo version 12 Plus was utilized to code and analysis of all interviews. Results: Five broad themes were identified: the role of the chief pharmacist; their attitudes towards the CPS; the advantages and results of the CPS; the barriers towards CPS; and their suggestions toward CPS. Most of the participants believed that the chief pharmacist played a vital role in a hospital. Under CPS, the hospital pharmacy department pays more attention to prescription review, medication monitoring, and pharmaceutical consultation. However, an insufficient number of pharmacy personnel, unclear authority, and inadequate salaries were the main barriers to the implementation of the CPS. Conclusions: The attitudes of most of the participants were found to be positive towards CPS in China. The CPS can enhance the prestige of the hospital pharmacy department, improve the quality of hospital pharmaceutical services, and promote rational drug use. Nevertheless, certain barriers highlighted in this study should be addressed promptly.